"O futuro não é mais como era antigamente": o rock nacional e o ensino de História. - Chilles Xavier, Fábio (2018)
This work is an action research that sought identify possible contributions of national rock music of teaching History from the work as a teacher in a private school in region of Itapetininga. Music was understood here, on one hand as a product of the cultural industry, from the Adornian perspective; and on the other hand as an important object of cultural mediation linked to socio-interactionist conceptions of Lev Vygotsky. Thus, having main objetive the possibility of use sophistication concepts such as "conscience" and "historical empathy", addressed by John Rüsen and Peter Lee at History tutorship. We sought to analyze the contributions of a didactic sequence developed with students of the first and second year of high school, on the contents "Invasion and Colonization of Brazil" and "Industrial Revolution", having as support the songs "Índios", "Fábrica" and "Captain of Industry"; of bands Legião Urbana and Os Paralamas do Sucesso. Among the results obtained, based on the analyzes by students during the process was possible conclude that work carried out provided for mental formulations among these students who showed involvement with historical agents of other temporalities and relevant conceptual appropriations of historical themes and having music as one of the learning axes. In general, spontaneous concepts were with the aid of the songs transformed into scientific concepts.